Deep ethnobotanical survey of Anise (Pimpinella anisum L.) in Morocco: variation of therapeutic uses, sources of information, and efficacy - Soussi, Meriem; El Yaagoubi, Wissal; benjelloun, Meryem; El Ghadraoui, Lahsen (Ethnobotany Research and Applications, 2023)
Background: An extensive ethnomedicinal analysis of anise (Pimpinella anisum L.) in Morocco was conducted as part of this study. We aimed to compile information on its medicinal uses and the amounts consumed by locals. Methods: Interviews were conducted in seven Moroccan sites during 2019 and 2020. To examine the gathered data, descriptive and multivariate statistics were employed. We sought participant agreement on the specified therapies for each disorder group. Results: 85 herbalist males and 600 participants ranging from 20 to 60 years old were interviewed in the study zone that uses or sells it for therapeutic purposes. The plant was primarily utilized by herbalists for food (18.93%), digestive disorders (18.93%), and laxatives (18.93%), while users use it for Dysmenorrhea (34.85%), anti-constipation (33.02%), antitussive (21.31%), and to promote Milk flow (10.82%). Other users used anise as an antitussive (12.47%) and a treatment for Dysmenorrhea (15.81%), while 14.92% of participants used it to encourage milk flow. Participants used the plant in dried form alone, and the usage form was like a Tisane or infusion in all investigated sites. However, all studied parameters varied among the tested sites. Conclusions: The new study could be of great use in expanding knowledge of the medicinal flora and conserving ancestors' knowledge in Morocco's Middle Atlas and the Saiss Plain.